Effects of Foreign Presence in a Transition Economy: Regional and Industrywide Investments and Firm-Level Exports in Ukrainian Manufacturing - Talavera, Stefan Lutz, Oleksandr (Emerging Markets Finance & Trade, 2008)
We investigate the effects of regional and industrywide foreign presence and foreign direct investment (FDI) on the export volumes of Ukrainian manufacturing firms using unpublished panel data from 1996–2000. Foreign presence through FDI may have negative competition effects on domestic firms' performance; at the same time, domestic firms' productivity may be increased by technology transfer or training and demonstration effects. From a Cournot competition model that includes negative competition and positive technology spillover effects, we hypothesize that foreign presence and FDI might positively affect domestic firms' output and exports. Our estimation results support these hypotheses, suggesting in particular that large firms and durable goods producers benefit most from foreign presence and investments.